Optimization of Stirling generator for the production of electric energy using non-aggregate methods - Victor Zogbochi; Patrice Koffi Chetangny; Mawuena Medewou; Sossou Houndedako; Gerald Barbier; Didier Chamagne (Scientific African)
The electrification policy adopted by many countries called “off-grid electrification”, consists of producing electrical energy where it is consumed from renewable sources. Among the methods of converting thermal energy into electricity, hot air engines (Stirling type) occupy a dominant place because they find their applications both in the renewable energy sector and in the recovery of waste heat. The aim of this work is to develop an optimal model of a generator consisting of a Stirling engine and an axial flux permanent magnet generator which will be easily displaceable and adapted to all hot primary sources. The β type Stirling engine is considered in this research. The objective is to design a compact mobile machine, accessible to households and capable of producing a minimum electric power of 2 kW under a temperature difference ∆T ≤ 1000 ° K. The artificial Bee Swarm Optimization Algorithm is used to determine the optimal mechanical power of the Stirling engine. This power constitutes the input variable of the generator model to determine the electrical power and the overall efficiency of the generator set. The results proved that for a temperature difference (∆T) of 600°K between the hot and cold heads, we obtain an electrical power of 4 kW corresponding to an overall efficiency of 31 %. The effect of hot head temperature variation and cylinder volume ratio where also considered for the global performance of the generator.